2015
DOI: 10.1021/acsami.5b02080
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Holographic Patterns on Azopolymers for Guiding Cell Adhesion and Orientation

Abstract: Topography of material surfaces is known to influence cell behavior at different levels: from adhesion up to differentiation. Different micro- and nanopatterning techniques have been employed to create patterned surfaces to investigate various aspects of cell behavior, most notably cellular mechanotransduction. Nevertheless, conventional techniques, once implemented on a specific substrate, fail in allowing dynamic changes of the topographic features. Here we investigated the response of NIH-3T3 cells to rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…The three‐dimensional (3D) dynamics of biological specimens, such as organoids, can be diverse, complex and challenging to assess precisely . Previous work on the mechanical environment's influence on cell behavior involves the use of microbumps , topographic signals and the polarization of ferroelectric materials . Although several studies have reported on the effects of cell cultures , no technique, to our knowledge, has been used to simultaneously tackle quantitative growth and mass transport.…”
Section: Introductionmentioning
confidence: 99%
“…The three‐dimensional (3D) dynamics of biological specimens, such as organoids, can be diverse, complex and challenging to assess precisely . Previous work on the mechanical environment's influence on cell behavior involves the use of microbumps , topographic signals and the polarization of ferroelectric materials . Although several studies have reported on the effects of cell cultures , no technique, to our knowledge, has been used to simultaneously tackle quantitative growth and mass transport.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in physiological conditions the photoinscribed topographies were unstable and could revert to their initial condition in a “shape‐memory” fashion . Rianna et al also used surface relief patterns on a glassy azo polymer for culturing NIH‐3T3 murine fibroblasts, attempting to exploit the erasure of azo polymer photopatterning using light . 1D‐ and 2D‐gratings with different periods were inscribed on the azo material ( Figure a) and an incoherent light source (a 15 mW mercury lamp) filtered in the blue region provided erasure, forming ordered microbumps at the surface, forcing cells to align along this new topographical cue.…”
Section: Interfacing Azo To Bio: An Eye Toward Influencing Living Sysmentioning
confidence: 99%
“…[25][26][27][28][29] When dealing with 2D light-responsive substrates, topographies can be instructed by a direct laser writing exposure of azopolymeric films previously spun on planar glass substrates. [31][32][33] As an alternative, projection masks [34] or laser interference lithography can be used. [31][32][33] As an alternative, projection masks [34] or laser interference lithography can be used.…”
Section: Doi: 101002/advs201801826mentioning
confidence: 99%